New approach to the resolution of triangular fuzzy linear programs: MOMA-plus method. - COMPAORE, Abdoulaye; SOME, Kounhinir; SOME, Blaise (International Journal of Applied Mathematical Research, 2017)
In this paper, we propose a new approach to the resolution of linear programs, whose coefficients are fuzzy triangular numbers. This new approach is an adaptation from the method MOMA-plus (Multi-Objective Metaheuristic based on Alineor method) [1] to the resolution of fuzzy linear programs. First of all it consists in using of a new procedure proposed here to the converting of the fuzzy linear program into a deterministic multi-objective linear program, secondly of the using of the MOMA-plus procedure for resolution. Finally, three numerical examples are given to explain the procedures and highlight the performances of this new approach.